1977
DOI: 10.1001/archderm.113.6.801
|View full text |Cite
|
Sign up to set email alerts
|

Atopic dermatitis and impaired neutrophil chemotaxis in Job's syndrome

Abstract: A 22-year-old white woman with Job's syndrome was found to have atopic dermatitis and impaired neutrophil chemotaxis in vitro. Major clinical features of Job's syndrome included large, "cold" and recurrent staphylococcal abscesses, and intermittent bacterial and yeast infections. Evidence for atopic disease included infantile eczema progressing to flexural dermatitis, a family history of atopy, positive immediate hypersensitivity skin tests, and hyperimmunoglobulinemia E. Defective erythema responses to histam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1978
1978
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…This aspect of the HIES phenotype is consistent with defective neutrophil function and, in fact, neutrophils isolated from HIES patients are reported to have impaired chemotaxis. 49 We found that STAT3-deficient mice are susceptible to L monocytogenes, failing to show early (12 hours) clearance of bacteria in liver or resolution of infection after 8 days, unlike their WT counterparts (data not shown). The innate immune response, mediated by neutrophils and macrophages, is particularly critical for suppressing early phases of infection with L monocytogenes.…”
Section: Discussionmentioning
confidence: 79%
“…This aspect of the HIES phenotype is consistent with defective neutrophil function and, in fact, neutrophils isolated from HIES patients are reported to have impaired chemotaxis. 49 We found that STAT3-deficient mice are susceptible to L monocytogenes, failing to show early (12 hours) clearance of bacteria in liver or resolution of infection after 8 days, unlike their WT counterparts (data not shown). The innate immune response, mediated by neutrophils and macrophages, is particularly critical for suppressing early phases of infection with L monocytogenes.…”
Section: Discussionmentioning
confidence: 79%
“…tissue margination) . Importantly, the human immunodeficiency condition Hyper‐immunoglobulin E syndrome (HIES), associated with inactivating mutations in one allele of STAT3 , is reported to show defects in neutrophil chemotaxis . Much remains to be learned about neutrophil function in HIES, however these data suggest specific STAT3 functions may be conserved in humans.…”
Section: Roles For Stats In Neutrophil Development and Functionmentioning
confidence: 99%
“…However, candidal and staphylococcal infections in HIES are limited to the skin and lung, suggesting that perhaps the neutrophils are functional but perhaps not trafficking to the site of infection. Indeed, numerous studies have demonstrated defective neutrophil chemotaxis in patients with HIES [3334]. HIES T-cell supernatant was not able to induce CXCL8 production by human bronchial epithelial cells or keratinocytes but was able to induce its production by fibroplasts and HUVECs, suggesting that in HIES patients, the skin and lung may be preferentially unable to adequately recruit neutrophils in a timely manner [35].…”
Section: Hies Pathogenesismentioning
confidence: 99%